Towards a Greener Chinatown: Re-Visioning a Culturally-Responsive and Inclusive Public Space System in Boston's Chinatown. - Guo, Rui. (2017)
Abstract: Public spaces are of great significance in densely urbanized areas for their environmental and social benefits to the communities. Throughout Boston's Chinatown's history, the neighborhood strove to preserve its historic landscape and improve its quality of life. But development encroachment from adjacent areas and nearby downtown has resulted in a severe lack of good public spaces to satisfy the needs - either environmental, social, or cultural - of its residents and visitors. This thesis aims to propose a redesign framework that would reconfigure Chinatown's public space system so that it responds to the rich cultural and historic heritage of the community, interacts inclusively with a diverse population, and promotes sustainability along multiple dimensions. Existing public spaces were reviewed and in-depth public outreach was conducted. A set of guiding principles was established to help develop a comprehensive redesign framework. Sites were selected to illustrate how the redesign framework could be applied, and specific design scenarios were visualized. Recommendations on funding, community collaboration, and future planning effort are provided.; Thesis (M.A.)--Tufts University, 2013.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Julian Agyeman.; Committee: Christine Cousineau.; Keyword: Urban planning.